Efisiensi Pupuk dan Peningkatan Hasil Padi Gogo dengan Aplikasi Pupuk Hayati dan Arang Tempurung Kelapa - Betty Natalie Fitriatin; Tien Turmuktini; Muhamad Iqbal Kusma Sudana; Dzakaria Yogaswara; Randy Nugraha (Soilrens, 2020)
The intensive application of inorganic fertilizers has a negative impact on soil health. Furthermore, the price of inorganic fertilizers has increased hence the production costs will also increase. Efforts to improve fertilizer efficiency and encourage environmentally friendly crops can be done by application of biofertilizers and organic ameliorants. The field experiment has been carried out to study the effect of biofertilizers application and coconut shell charcoal to increase inorganic fertilizers efficiency and yield of upland rice at Rancakalong, Sumedang, West Java. The experiment used factorial randomized block design consisted two factors. The first factor were biofertilizers and coconut shell charcoal and the second factors were inorganic fertilizers doses. Biofertilizers with consortia of Azotobacter chroococum, Azospirillum sp., Pseudomonas mallei, Burkolderia sp., Aspergillus niger, and Penicillium sp. and organic ameliorant was coconut shell charcoal. NPK fertilizers were applied in 25%, 50%, 75% and 100% of recommended doses. The results revealed that biofertilizers and coconut shell charcoal increased growth and yield of upland rice. This finding concludes that applica